PtCu catalyst synthesis via Cu oxide-mediated carbon etching and alloying strategy for enhanced ORR - Choi, Yuna; Jung, Jae Young; Kim, Dong-gun; Kim, Nam Dong; Park, Subin; Lee, Eungjun; Yoo, Sung Jong; Kim, Pil (American Ceramic Society, 2026)
Enhancing both the activity and durability of oxygen reduction reaction (ORR) is essential for the advancement of proton exchange membrane fuel cells (PEMFCs) in practical applications. In this study, we present a novel strategy to synthesize highly dispersed PtCu alloy nanoparticles (NPs) within etched carbon supports using copper oxides seed-mediated carbon oxidation. The sacrificial Cu-based seeds not only facilitated the carbon etching process but also enabled controlled placement of PtCu NPs while preventing aggregation. The resulting PtCu catalyst demonstrated a high half-wave potential (0.931 VRHE), with an electrochemical active surface area of , comparable to commercial Pt/C (). Interestingly, mass activity and specific activity of PtCu catalyst reached and 1128 mu A cm-2 at 0.9 VRHE, representing 3.4-fold and 3.5-fold enhancements compared to commercial Pt/C. After accelerated durability testing (20 000 CV cycles), the catalyst exhibited the mass activity of and specific activity of 871 mu A cm-2 at 0.9 VRHE, indicating outstanding electrochemical stability. This work demonstrates the critical role of seed-mediated PtCu NP synthesis in developing high-performance and durable ORR catalysts, offering a promising route for next-generation PEMFC electrodes.